Efgartigimod: First Approval - Heo, Young-A (Drugs (New York, N.Y.), 2022)
Efgartigimod (efgartigimod alfa-fcab, Vyvgart ™ ) is a first-in-class neonatal Fc receptor antagonist being developed by argenx for the treatment of autoimmune diseases including myasthenia gravis. In December 2021, intravenous efgartigimod received its first approval in the USA for the treatment of generalized myasthenia gravis in adults who are anti-acetylcholine receptor (AChR) antibody positive. Intravenous efgartigimod has also been evaluated for generalized myasthenia gravis in various other countries, with the agent subsequently approved in Japan in January 2022 for generalized myasthenia gravis patients regardless of antibody status and in preregistration stage in the EU. Several clinical studies of intravenous and subcutaneous formulation of efgartigimod are also being investigated for other autoimmune diseases including bullous pemphigoid, chronic inflammatory demyelinating polyradiculoneuropathy, immune thrombocytopenia, autoimmune myositis and pemphigus. This article summarizes the milestones in the development of efgartigimod leading to this first approval for generalized myasthenia gravis.